ANALISIS KARAKTERISTIK SAMPAH DALAM MENENTUKAN OPTIMALISASI KINERJA PENCACAHAN DI TPS 3R KESIMAN KERTALANGU - Sastra Wibawa, I Made; Maharani, Shinta Enggar; I Nyoman Waisnawa Budiswara (Jurnal Ecocentrism, 2024)
The increasing population causes an increase in the amount, variety and characteristics of waste. Good waste processing and management is needed to deal with waste problems. TPS 3R Kesiman Kertalangu is an independent waste processing site in Kesiman Kertalangu Village. There is mixed and residual waste entering TPS 3R Kesiman Kertalangu. In processing the waste into compost, the waste is first sorted and shredded. In this research, several experiments were carried out to determine the maximum sorting and shredding speed. The water content of the waste studied included: 25%, 50%, 75%. The research method used is the experimental method. Determining the water content of waste is done first by observing the daily weather to obtain the desired water content. Apart from that, there is a wash out of sorting personnel in sorting waste to get accurate data, so that there is no carry over effect. Measuring shredding speed uses the SNI 7580:2010 approach as a reference that is close to the basis of research. Based on research results, waste water content of 25% is the maximum waste for sorting. Apart from that, waste with a water content of 25% is also the waste that is shredded the fastest.